2011
DOI: 10.1039/c0lc00222d
|View full text |Cite
|
Sign up to set email alerts
|

Fast microfluidic temperature control for high resolution live cell imaging

Abstract: One major advantage of using genetically tractable model organisms such as the fission yeast Schizosaccharomyces pombe is the ability to construct temperature-sensitive mutations in a gene. The resulting gene product or protein behaves as wildtype at permissive temperatures. At non-permissive or restrictive temperatures the protein becomes unstable and some or all of its functions are abrogated. The protein regains its function when returning to a permissive temperature. In principle, temperature-sensitive mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 36 publications
0
52
0
Order By: Relevance
“…Fast temperature shift of the cdc31-8 mutant was performed under the microscope (Velve Casquillas et al, 2011). The cell cycle stage at the time of temperature shift was defined according to microtubule organization, using the fluorescent tubulin marker GFP-Atb2 (Atb2 is also known as Tub1) (Fig.…”
Section: Half-bridge Duplication Might Be Initiated During Anaphasementioning
confidence: 99%
“…Fast temperature shift of the cdc31-8 mutant was performed under the microscope (Velve Casquillas et al, 2011). The cell cycle stage at the time of temperature shift was defined according to microtubule organization, using the fluorescent tubulin marker GFP-Atb2 (Atb2 is also known as Tub1) (Fig.…”
Section: Half-bridge Duplication Might Be Initiated During Anaphasementioning
confidence: 99%
“…The temperature control system used in our devices consists of a large chamber (7 × 16 mm) through which a flow of water pre-thermalized by Peltier elements is constantly maintained [33]; this chamber is positioned above the cell compartment (figure 6 a ). It was produced by cutting 81 µm thick double-sided tape (ARcare 90445) using a 60 W CO 2 laser cutter (Speedy 100, Trotec, Austria).…”
Section: Methodsmentioning
confidence: 99%
“…29,30 Moreover, many welldeveloped microfluidic manipulation and detection techniques could be incorporated into the microreactors for in-line monitoring of the intermediate and final products. 16,30,45 V. CONCLUSIONS A photocatalytic microreactor system was constructed by directly mounting a blue-light LED panel on a microfluidic planar reactor, which enables to make use of both the heat and the light energy for organic degradation. Experimental studies have shown that the microreactor facilitates the control of photocatalytic process by adjusting the LED light intensity and the flow rate.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] The great success of microfluidics in many applications such as chemical analysis, biomedical assay, and drug screening has well demonstrated its remarkable capabilities in dealing with particles, fluids, and light in an integrated platform. [7][8][9][10][11][12][13][14][15][16] Thanks to its merits of flexible flow control, large surface-area-to-volume ratio, and compact size, the microfluidics could benefit the photocatalysis [16][17][18][19][20] in various aspects such as fast mass a) E-mail: apzhang@polyu.edu.hk. Tel.…”
Section: Introductionmentioning
confidence: 99%